Prevalence of risk factors of non-communicable diseases in Kerala, India: results of a cross-sectional study - P S Sarma; Rajeev Sadanandan; Jissa Vinoda Thulaseedharan; Biju Soman; Kannan Srinivasan; R P Varma; Manju R Nair; A S Pradeepkumar; Panniyammakal Jeemon; K R Thankappan; Raman V Kutty (BMJ Open)
Objective To estimate the prevalence of non-communicable disease (NCD) risk factors in Kerala.Design A community-based, cross-sectional survey.Participants In 2016–2017 a multistage, cluster sample of 12 012 (aged 18–69 years) participants from all 14 districts of Kerala were studied.Main outcome measures NCD risk factors as stipulated in the WHO’s approach to NCD risk factors surveillance were studied. Parameters that were studied included physical activity score, anthropometry, blood pressure (BP), and fasting blood glucose (FBG) and morning urine sample to estimate dietary intake of salt.Results The mean age was 42.5 years (SD=14.8). Abdominal obesity was higher in women (72.6%; 95% CI 70.7 to 74.5) compared with men (39.1%; 95% CI 36.6 to 41.7), and also higher among urban (67.4%; 95% CI 65.0 to 69.7) compared with rural (58.6%; 95% CI 56.6 to 60.5) residents. Current use of tobacco and alcohol in men was 20.3% (95% CI 18.6 to 22.1) and 28.9% (95% CI 26.5 to 31.4), respectively. The estimated daily salt intake was 6.7 g/day. The overall prevalence of raised BP was 30.4% (95% CI 29.1 to 31.7) and raised FBG was 19.2% (95% CI 18.1 to 20.3). Raised BP was higher in men (34.6%; 95% CI 32.6 to 36.7) compared with women (28%; 95% CI 26.4 to 29.4), but was not different between urban (33.1%; 95% CI 31.3 to 34.9) and rural (29.8%; 95% CI 28.3 to 31.3) residents. Only 12.4% of individuals with hypertension and 15.3% of individuals with diabetes were found to have these conditions under control. Only 13.8% of urban and 18.4% of rural residents did not have any of the seven NCD risk factors studied.Conclusion Majority of the participants had more than one NCD risk factor. There was no rural–urban difference in terms of raised BP or raised FBG prevalence in Kerala. The higher rates of NCD risk factors and lower rates of hypertension and diabetes control call for concerted primary and secondary prevention strategies to address the future burden of NCDs.